The Influence of the level of water availability in the soil on the growth and production of two varieties of corn (Zea Mays L) - Drasto Laksono; Ida Agustinio Saidi (Universitas Muhammadiyah Sidoarjo, 2016)
Production of corn plants in Indonesia is still low, due to constrained uncertain seasons. The main problem is not insufficient water in the soil for plant growth. The study aims to determine the level of water availability in the soil on the growth and yield of two varieties of corn, conducted from February to June 2016 in the village juwet Kenongo Porong Sidoarjo. With an average temperature of 31C and a humidity of 44%. Research using a completely randomized design (CRD) arranged as factorial with two (2) factors and 3 (three) replications. The first factor is a variety that consists of, V1 (Variety Bhishma), V2 (Variety Arjuna). The second factor is water availability level consists of three levels, namely P1 (30%), P2 (60%), P3 (90%). From the second treatment factor is obtained as 6 treatment combinations. The results showed that no interaction between the two treatments of soil moisture in the soil of the two varieties of crops to dry seed weight. Interaction of the two treatments only occur at the root length parameter. Varieties effect on parameter number of leaves at the age of 29 HST, 36 HST 43 HST, whereas the availability of water affects the parameters of the number of adventitious roots.